Repeated Implementation - Ehud Kalai; John O. Ledyard (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
In the traditional static implementation literature it is often impossible for implementors to enforce their optimal outcomes. And when restricting the choice to dominant-strategy implementation, only the dictatorial choices of one of the participants are implementable. Repeated implementation problems are drastically different. In this paper we provide an implementation "folk theorem": for patient implementors, every outcome function they care about is dominant-strategy implementable.
Keywords: 330